Islamic Khilafah (Caliphate) in the History of Muslim Civilization: The Conflict Between Sunni and Shi’i - Fadzli, Adam; Engku Muhammad Tajuddin, Engku Ali (2014)
On the basis of teachings found in the Qur’an and in certain hadiths, many traditional Muslims have claimed that Islam provides guidelines for the formation and propagation of the caliphate (khilafah). This claim, however, remains a matter of some contention and the issue has provoked much argument and debate among Muslim communities. From the beginning of the Islamic khilafah to the present day (excluding the khilafah of the Prophet, which Muslims accept as the most perfect model), Muslims’ understanding and application of the concept has been overshadowed by uncertainty and dispute. This article intends to arrive at a more precise understanding of the historical overview for the caliphate and to present the chronology of the issue from the perspective of several Islamic periods using content analysis approach. However, it does not intend to decide which model of Islamic caliphate is the best or the most suited to the original teaching of the Prophet Muhammad (peace be upon him). Rather it will investigate the differences and agreements to be found among Sunni and Shici Muslims and especially between the Sunni and the Imamiyyah Ithna Cashariyyah from the seventh to the fourteenth centuries and in the twentieth century.